Freedom of Expression on Social Media from Human Rights and ITE Law Perspectives - Dian Ayu Rahmadani; Nurazizi Nafisha (Penerbit Goodwood, 2026)
Purpose: This research is intended to examine the freedom to express oneself as one of the fundamental human rights guaranteed by the 1945 Indonesian Constitution and to examine its application in the use of social media from the perspective of the Electronic Information and Transactions Law (ITE Law). Research Methodology: This study uses a qualitative approach with a literature review method by analyzing relevant academic sources, including journals, books, and statutory regulations. Results: Findings indicate that social media has expanded the public space for expressing opinions, ideas, and criticism as part of democratic life. However, the implementation of the ITE Law, particularly provisions regarding defamation and hate speech, often gives rise to multiple interpretations, leading to legal issues and potentially hampering freedom of expression on digital platforms. Conclusions: Freedom of expression on social media requires a balance between protecting individual rights and maintaining public peace. Therefore, clearer legal guidelines are needed to prevent multiple interpretations in the application of the Information and Communication Technology Law (ITE Law). Limitations: This study is limited to a literature review and does not involve empirical data, so it may not fully reflect real conditions. Contributions: This study contributes to legal scholarship by providing insights into the relationship between human rights and digital regulation and may serve as a reference for academics, policymakers, and the public.